PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG DI RUMAH SAKIT KARISMA CIMAREME - Refian Nugraha Saputra (POLITEKNIK PIKSI GANESHA, 2021)
The hospital has made arrangements for the supplies stored in its operational activities. However, hospitals are still experiencing difficulties in improving inventory management so that they can run optimally. This happens because the hospital is still implementing a manual inventory recording system, causing inventory information carried out at the hospital in inaccurate inventory recording. The purpose of this research is to create an information system to overcome these problems. The study began by analyzing qualitative data about the current system at Karisma Cimareme Hospital, the authors used observation and interviews with hospital employees and owners, as well as adding research supporting theories using the waterfall method, and using the Microsoft Visual Studio 10 program as software and Microsoft Access to process the data.